A modified basis reduction method for limited kinematic hardening shakedown analysis under complex loads. Issue 1 (2nd January 2018) - Huang, Song; Wan, Futeng; Jiao, Peng; Chen, Zhiping
ABSTRACT: A novel extension of the basis reduction method for kinematic hardening shakedown problem is presented. Firstly, the basis reduction method is implemented based on the modified Newton–Raphson (N-R) method. Then a new technique for the construction of back stress field is introduced, where the simultaneous influence of multiple load corners in shakedown is taken into consideration. Finally, two typical numerical examples are investigated. The results compared with previous works in literatures demonstrated that the proposed method is accurate and the performance in reducing of computation time is significant.